Decellularization of meniscal tissue using ultrasound chemical process for tissue-engineered scaffold applications - Noor Azmi, Azran Azhim; Takahashi, T.; Muramatsu, K.; Morimoto, Y.; Tanaka, Takanori (Springer Berlin Heidelberg, 2010)
Scaffolds play a key role in the process of regeneration and morphogenesis of tissue or organ. We have studied a novel application of ultrasound irradiation to prepare decellularized tissue for tissue-engineered scaffolds. The aim of the present study is to investigate the possibility of ultrasound energy on decellularization of cartilage tissue. The samples were decellularized using 20 kHz of ultrasonic irradiation in circulated 0.3% sodium chloride (NaCl) constituent of 2% sodium dodecyl sulfate (SDS) solution. To evaluate tissue integrity and cell removal, we used hematoxylin-eosin staining. To estimate the degree of irradiated ultrasound on the sample, we used computer simulation to calculate the irradiated power distribution in solution, corresponding to the irradiation energy against to the sample. From histological results, it shows that the ultrasonic power could assist the decellularization on meniscal tissue. The decellularization efficiency was better than the other preparation methods. Because of distributions of ultrasonic irradiation to samples were non-uniform, the efficiency of cell removal could be improved by using 3 dimensional scanning system which uniformly irradiate to the sample. In conclusion, ultrasonic chemical process has a potential to improve the efficiency of decellularization for menisci.